KELIMPAHAN SIPUT GONGGONG (Strombus spp) YANG BERASOSIASI DENGAN PADANG LAMUN DI PANTAI DESA TUKAK KABUPATEN BANGKA SELATAN - OKTO SUPRATMAN; DWI ROSALINA; WAHYU ADI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2014)
Gonggong snails is a type of sea slug that has long been known to the public of Bangka Belitung. That has a fairly high economic value and is the typical food of Bangka Island, known as crackers gonggong snails . This is why this biota often hunted excessively without loss of control that affect populations decrease in nature. This research aims to know the abundance of gonggong snails associated with seagrass in the coastal Tukak village and the relationship between gonggong snails abundance with the seagrass ecosystems. Research was conducted in March-August 2011 at the Coast Tukak Village. Data retrieval consists of three stations, where each station is divided into three substations, each substation consists of three transect squares. Data taken included closure per type of seagrass, totally closure of seagrass, all types of gonggong snails and the water physico-chemical parameters. The results of physics and chemical parameters obtained water temperature ranges from 31-340C, 100% brightness, depth of 21-33 cm, flow rate from 0.027 to 0.051 m / s, pH 7.5 to 8, salinity 28-330/00 with a sandy mud bottom substrate . Gonggong snails that found on the research site is only one type of species of Strombus canarium, including Strombidae Family, Classes of Gastropoda in Mollusca phyllum. The size of gonggong snail shells that found at the research site approximately ranged from 6.9 to 8.1 cm and 0.1 to 0.8 pcs/m2 abundance with a random distribution patterns tend to cluster. Relations density/closure of seagrass with an abundance of gonggong snails does not have a significant relationship. The species of seagrasses also affect gonggong snails abundance, there are 6 species of seagrass found in the Coastal Tukak Village is Cymodocea rotundata, Cymodocea serrulata, Thalassia hemprichii, Enhalus acoroides, Halodule uninervis and Halophila minor. Of the six types of seagrass found in only three seagrass species are positively related to the abundance of gonggong snails, that is Halodule uninervis, Halophila minor and Enhalus acoroides